Cultural Heritage Protection and Revitalization of its Local Wisdom: A Case Study - Kartono, Kartono; Fadilah, Muhammad; Yuliantiningsih, Aryuni; Thakur, Anupriya (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2024)
Banyumas Old Town, once the capital of the district, is home to numerous historical buildings recognized as cultural heritage or potential cultural heritage sites. Since 2010, this area has been designated as a protected zone focused on environmental preservation. This research aims to describe and analyze the policies implemented for the preservation the historic buildings in Banyumas Old Town, as well as to identify and address the challenges faced in the preservation efforts. Utilizing legal research methods, particularly a case study approach, the study employs qualitative analysis. The data include secondary sources, comprising both primary and secondary legal materials. Additionally, field data were collected through observations and interviews. The findings indicate that the revitalization plan for Banyumas Old Town has been successfully implemented. Key action include designating the Banyumas sub-district as a protected area, conducting an inventory of suspected cultural heritage objects (ODCB), officially recognizing cultural heritage sites, and securing funding through the local government budget (APBD). These policies are formalized through the establishment of regional spatial planning and cultural heritage regulations. The primary obstacle to protecting cultural heritage buildings is the significant number of sites that have been privatized, alongside the limited opportunities for transferring cultural heritage or ODCBs that have received government renovation support following the revitalization of Banyumas Old Town.